Construction of Business Intelligence Model for Information Technology Sector with Decision Support System (Journal of Information Technology and Digital World, 2022)
Understanding and evaluating data is vital for making choices in a system. As the transactional system expands, it becomes increasingly difficult to execute analytical operations directly. Complex and huge datasets seem to be solved by analytical methods and their expansions. A lack of a clear and rigorous technique for measuring the realized value of intelligent business systems continues to be a problem, despite the fact that significant investment is being made in these systems. As a goal of the software program, an inventory management decision support system has been built. The method can be used by medium-sized industries or companies. Finding a suitable solution for the firm's size and adapting to business and decision-maker needs are the goals of this research work. Besides, the suitable solutions are measured and compared with reference data through Information Technology (IT) sectors by error computations. The computation has considered various types of errors in this research article. The proposed decision support system produces excellent results with the least amount of errors in the final output, as shown by the graphical depiction in the results and discussion section.
Keywords: Business Intelligence; decision support system; information technology; Business management; business maintenance